Konstruksi Pendekatan Saintific Dalam Pembelajaran Pendidikan Agama Islam Di SMK Perpajakan Riau - Hatta, M.; Subairi, Agus; Amin, Muhammad (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
The construction in this study is in order to explore the usefulness of applying the scientific system learning in PAI learning at the Riau Taxation Vocational School. The method used is a research experiment with a study subject of PAI teachers totaling 1 person. With the conclusion of the research, namely: 1) the scientific approach in PAI learning has a significant impact on the learning process through five elements namely: (1) observing, (2) asking, (3) experimenting (4) association and (5) reasoning. This is illustrated by the findings that PAI teachers are able to provide learning by attracting students' attention, high motivation from students, being able to provide references and mapping PAI discussions. 2) PAI teachers are able to bring up critical learning as a scientific form. The research findings were confirmed through John Dewey's theory which put forward the following: 1) positing problems, 2) clarifying issues, 3) looking at the possible answers of students together with educators looking for possibilities that will be implemented in problem solving, 4) try out the possibilities that are considered profitable, 5) assessment. From these objectives it can be concluded that several dimensions are to be improved and addressed by learning activities of Islamic religious education, namely: a) Dimensions of students' faith in Islamic teachings. b) The dimensions of understanding or reasoning (intellectual) as well as students' knowledge of Islamic teachings. c) The dimension of appreciation or inner experience felt by students in carrying out Islamic teachings